Burden of proof of the exclusions of unlawfulness in the criminal process and the necessity to break with its civil origin - Nogueira, Rafael Fecury (2018)
The present work proposes a critical analysis about the burden of proof of the exclusion of unlawfulness in criminal procedure, researching about the responsible for it, whether prosecution or defense. Traditionally, in Brazil, the jurisprudential orientation links the burden of proof of the exclusion of unlawfulness to the defendant. This link happens because the exclusion of liability’s cases is equated to the civil theory about impeding, modifying or extinguishing rights facts. The following study is focused in the origin of the theses that allowed the construction of the current conception. This method enables to compare the civil and the criminal rules concerning to the burden of proof. For a detailed understanding of the subject, it is necessary to carry out a historical course of dogmatic aspects specific to civil procedural law and criminal law that converge to the current theme, such as the rule of distribution of the burden of proof in the civil procedure and the evolution of crime’s theory.